The Influence of Right Speech (Samma Vaca) on the Communication Ethics of Buddhist Students on Social Media - Paramita, Santi; Wulan, Cening Ayu; Widiyanto, Widiyanto; Saputri, Vike Aprilianin Marwintaria; Avitasari, Iin; Yudhawati, Ine (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2025)
This study aims to examine the influence of correct speech (Sammā Vācā) a key principle in Buddhist ethics on the communication behavior of Buddhist students in Lampung. Using a quantitative approach with a survey method, data were collected from 98 Buddhist students who actively use social media. A structured questionnaire based on a Likert scale was used and analyzed through relevant statistical tests, including validity, reliability, and simple linear regression. The findings show that correct speech significantly influences communication ethics, with a determination coefficient of 0.532, indicating that 53.2% of students’ communication ethics are affected by their understanding of Sammā Vācā. These results highlight the importance of integrating Buddhist moral teachings into digital literacy education to foster respectful and ethical online communication aligned with Dhamma values.